PRAKTIK PENJUALAN PENGANTIN ANAK DI AFGANISTAN MENURUT PROTOKOL OPSIONAL KONVENSI HAK-HAK ANAK - Elya Almadinatulmunawaroh; Andrey Sujatmoko (Reformasi Hukum Trisakti, 2023)
Children as a vulnerable group have the right to receive protection by the state, one of which is Afghanistan. In Afghanistan there have been several cases of selling exploitative children. The formulation of the problem in this research is how the efforts have been made by the Afghan government in dealing with the practice of selling child brides in Afghanistan according to the Convention on the Rights of the Child. The research method used in this study is normative juridical and descriptive-analytical in nature, the source of which is secondary data which is analyzed qualitatively, and conclusions are drawn using deductive methods. The conclusion in this study is that the act of selling child brides in Afghanistan is a practice of selling children which is prohibited according to the Optional Protocol to the Convention on the Rights of the Child regarding the Sale of Children, Child Prostitution, and Child Pornography. The efforts that have been made by the Afghan government have ratified the relevant legal provisions, but law enforcement against a number of cases of selling child brides is still not firm and has not been carried out in accordance with applicable law.